Autoethnographic Tourism Experience of Wheelchair User in Bali, Indonesia - Zobritania, Maudita; Widadsyah, Muhammad Azhar (The Center for Disability Studies and Services Brawijaya University, 2023)
This research presents autoethnography study of a wheelchair-users named Zo during her journey in Bali, Indonesia. Her documentations and field notes are analyzed in four main themes: information accessibility, public facilities accessibility, destinations accessibility as well as cultural and social issues. This research provides personal deeply personal view on her experience, her way to adapt with accessibility issues, as well as multiple accessibility issues that needs to be improved to ensure that all travelers are able to enjoy Bali.